PENGARUH LAMA WAKTU PERENDAMAN MENGGUNAKAN URINE SAPI TERHADAP PERKECAMBAHAN BIJI LAMTORO TARRAMBA (Leucaena leucocephala CV. Tarramba) - Susan Belipati; Thomas Lapenangga; Stormy Vertygo (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The study was conducted to determine the difference in immersion time in cow urine on the percentage of germination, the average germination rate and the rate of germination growth. This study used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments were P0: Immersion in cow urine without time, P1: Immersion in cow urine for 30 minutes, P2: Immersion in cow urine for 60 minutes and P3: Immersion in cow urine for 90 minutes. The parameters in this study were the percentage of germination, the average germination rate and the growth rate of germination. Data on percentage germination, mean germination rate and growth rate of germination were analyzed using Analysis of Variance (ANOVA) and for growth rate of germination continued using Duncan's test. The results showed that the immersion time of lamtoro seeds in cow urine had a significant effect (P<0.05) on the average germination rate, but had no significant effect (P>0.05) on the percentage of germination and growth rate of germination. The best result was given by P3 treatment that gave the highest germination rate of 0.525 seed/day compared to the control which was only 0.428 seed/day. Nonetheless, it is still recommended to use cow urine to immerse seeds for 90 minutes particularly to enhance its germination rate. This research could hopefully give a useful reference for farmers as an alternative method of technology in cultivating animal feed plants for a better and improved productivity.